Effect of growing media on the growth of stevia (Stevia rebaudiana (Bertoni) Bertoni) tip cuttings - Arif Gozali Warso Saputro; Muchamad Yusron; Raden Vitri Garvita; Gut Windarsih (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Stevia is 200-300 times sweeter than sucrose but low in calories, making it a safe alternative for individuals with diabetes or obesity. The utilization of stevia has the potential to reduce reliance on sugar imports. This research aimed to investigate the influence of different growing media on the growth of stevia tip cuttings. This study was conducted from August to December 2023 in Cidokom Village, Cisarua District, Bogor Regency, West Java. The method used was experimental research using a completely randomized design (CRD) with a single factor, which was the composition of the growing media. Six types of growing media were used. The research results showed significant differences among the treatment groups of growing media on various growth parameters of stevia tip cuttings. Stevia tip cuttings planted in soil and manure media showed the best results in cutting height (28.8 ± 2.82 cm) 42 days after planting. Meanwhile, the combination of solid waste agar, sand, mycorrhiza, burnt rice husks, and cocopeat media resulted in the highest number of leaves (22.20 ± 3.20 leaves) and total fresh weight of stevia tip cuttings, around 1.98 ± 0.33 g at 42 days after planting. Keywords: mycorrhiza; planting media; vegetative growth